A Genomewide Association Study Identifies Two Sex‐Specific Loci, at SPTB and IZUMO3, Influencing Pediatric Bone Mineral Density at Multiple Skeletal Sites. (2nd March 2017) - Chesi, Alessandra; Mitchell, Jonathan A; Kalkwarf, Heidi J; Bradfield, Jonathan P; Lappe, Joan M; Cousminer, Diana L; Roy, Sani M; McCormack, Shana E; Gilsanz, Vicente; Oberfield, Sharon E; Hakonarson, Hakon; Shepherd, John A; et al.
ABSTRACT: Failure to achieve optimal bone mineral accretion during childhood and adolescence results in subsequent suboptimal peak bone mass, contributing to osteoporosis risk later in life. To identify novel genetic factors that influence pediatric bone mass at discrete skeletal sites, we performed a sex‐stratified genomewide association study of areal bone mineral density (BMD) measured by dual‐energy X‐ray absorptiometry at the 1/3 distal radius, spine, total hip, and femoral neck in a cohort of 933 healthy European American children. We took forward signals with p  < 5 × 10 −5 and minor allele frequency (MAF) >5% into an independent cohort of 486 European American children in search of replication. In doing so, we identified five loci that achieved genome wide significance in the combined cohorts (nearest genes: CPED1, IZUMO3, RBFOX1, SPBT, and TBPL2 ), of which the last four were novel and two were sex‐specific ( SPTB in females and IZUMO3 in males), with all of them yielding associations that were particularly strong at a specific skeletal site. Annotation of potential regulatory function, expression quantitative trait loci (eQTL) effects and pathway analyses identified several potential target genes at these associated loci. This study highlights the importance of sex‐stratified analyses at discrete skeletal sites during the critical period of bone accrual, and identifies novel loci for further functional follow‐up to pinpoint key genes and better understand the regulation of bone development in children. © 2017 American Society for Bone and Mineral Research.